A Comparative Study of Solid Electrolyte Interphase Evolution in Ether and Ester-Based Electrolytes for Na-ion Batteries - Liang Zhao; Sara I.R. Costa; Yue Chen; Jack R. Fitzpatrick; Andrew J. Naylor; Oleg Kolosov; Nuria Tapia-Ruiz (PRX Energy)
The solid electrolyte interphase (SEI) largely determines the electrochemical performance of negative electrodes in sodium-ion batteries (SIBs). Ether-based electrolytes, such as diglyme, have been shown to form a more stable and thinner SEI on sodium anodes than traditional commercial ester-based electrolytes. Nonetheless, variations in the detailed evolution of the chemical composition and mechanical strength of the SEIs formed in these two electrolytic solutions during the electrochemical process have rarely been investigated. In this work, we conduct a comparative study of the SEI formed in diglyme-based and carbonate-based electrolytes with Na_{2}Ti_{3}O_{7} (NTO) as a proof-of-concept material, using energy-tuned photoelectron spectroscopy, operando electrochemical atomic force microscopy, and electrochemical techniques. The results show that diglyme forms a thin, homogeneous, and stable SEI with a well-defined inorganic-organic bilayer structure, as opposed to ester-based electrolytes, which form a thicker, nonuniform, and dynamically changing SEI with randomly distributed inorganic-organic structure. Moreover, the less resistive and higher capacitive interfacial processes induced by the diglyme-based electrolyte decrease the overall battery impedance. These advantages enable the NTO anode to exhibit superior specific capacity, cycle stability, and rate capability. This study provides an in-depth view of the factors behind the electrolyte-dependent performance of SIB anodes, which could inform the design and pairing of electrolytes with electrode materials in rechargeable batteries.